THE INFLUENCE OF SUBTITLES IN SHORT MOVIES ON STUDENTS’ LISTENING COMPREHENSION (A Quasi- Experimental Study in One of State Junior High Schools in Garut) - Amalia Audina; Anne Ratna Suminar (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This quasi-experimental study intended to figure out whether the subtitles in short movies influence students’ listening comprehension. To achieve the purpose, the data were collected through listening test. This nonequivalent control group design was conducted with 60 students of second grade in one of Junior High School in Garut. In terms of findings, the study revealed that subtitles in short movies had significant influence on students’ listening comprehension. It proves by the t’ test value of posttest that is tcount = 2.268 < tcritical = 2.0452. Therefore, it means that Ho was rejected and Ha was accepted. This study concluded that the subtitles in short movies offer potential benefit and may help on improving students’ listening comprehension.